FACTORS INFLUENCING THE ADOPTION OF CLOUD COMPUTING SYSTEMS IN E-TOURISM - Dewi, Dian; Harsono, Jusuf; Yulianti, Dwiana Binti; Desriyanti, Desriyanti; Jovita, Hazel (CosmoGov: Jurnal Ilmu Pemerintahan, 2022)
The development of technology, information, and computers is increasingly providing convenience and comfort for users. It is no different from the innovation of the e-Government concept carried out by the government in the tourism sector (e-Tourism). The purpose of this study was to determine the factors that influence the adoption of cloud computing systems in the development of tourism based on technology and information (E-Tourism). The research method used is a literature study with the help of the Nvivo 12 Plus analysis tool. The results show that the adoption of cloud computing systems in the development of E-Tourisme is certainly driven by the many advantages provided, including Ease of Access, Cost Efficiency, Flexibility in Adding Capacity, Ease of Server Monitoring and Management, Increasing Data Availability, Focus on Business Improvement and Business Development. In addition, cloud computing innovates in improving smartphone-based facilities and features. For users, the cloud system provides easy access along with GPS, camera, music player, a dictionary, notepad, and translator, a tourist need. gb777